A novel near‐infrared fluorescence probe for detecting and imaging Hg2+ in living cells. (25th November 2021) - Liang, Fanghui; Xu, Longbin; Jin, Danhong; Dong, Lidan; Lin, Shourui; Huang, Rui; Song, Daqian; Ma, Pinyi
Abstract: Fluorescence imaging, as one of the important means of biological lesion analysis, is widely used in medical analysis. To improve detection specificity, near‐infrared emission fluorescent probes have been developed. Sensitive and selective near‐infrared (NIR) fluorescent probes for Hg 2+, which is a heavy metal ion harmful to human health, are urgently needed to investigate the physiological toxicity of Hg 2+ . The NIR fluorophore based on the traditional structure of rhodamine was prepared by introducing anthocyanin functional groups, and a rhodamine spiro ring structure was constructed to recognize Hg 2+ (CCS–Hg). The probe CCS–Hg demonstrated good selectivity and high detection sensitivity for Hg 2+ and the most likely mechanism was verified through theoretical calculations. We applied the probe CCS–Hg in the examination of Hg 2+ distribution in living cells by NIR fluorescence imaging. This work provides a promising molecular tool for studying the toxicological effects of mercury ions in cell. Abstract : The NIR fluorophore based on the traditional structure of rhodamine was prepared by introducing anthocyanin functional groups, and a rhodamine spiro ring structure was constructed to recognize Hg 2+ (CCS‐Hg).